Determination of isolated Aeromonas hydrophila antibiotic resistance profile from farmed common carp (Cyprinus carpio) in khuzestan province - N Moori Bakhtiari email ; R Peyghan; F Monzavi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
Aeromonas are an example of emerging bacterial pathogens. Even though they have been recognized as primary fish and human pathogens. Aeromonas hydrophila are opportunistic pathogens that are at the same time infectious and enterotoxigenic and multiple antibiotic resistances (MAR) among Aeromonas hydrophila strains has been reported from many parts of the world. Under these circumstances, it will be worthwhile to find out the prevalence of antibiotic resistance of the Aeromonas hydrophila strains. The one hundred pieces of fish samples were collected from 4 common carp training pool in Khuzestan province. The part of intestine was collected in sterile plate and was homogenized. The samples were cultured in blood agar and incubated in 37centigrade degree temperature. Three to five Aeomonas hydrophila suspected colony, were selected from any plate and purified in blood agar. After initial evaluation of each colony by catalase, oxidase and gram staining, suspected strains DNA was extracted by boiling. Aeromonas hydrophila strains were confirmed by PCR assay and using of genus and species specific primers. Finally, multiple antibiotic resistance (MAR) of confirmed Aeromonas hydrophila isolates was evaluated by Kirby-Bauer disc diffusion method. Twenty Aeromonas hydrophila strains of Aeromonas suspected colonies were confirmed by PCR assay and the most of isolates had a multiple resistance. The least and the most resistance was observed regarding to cefotaxim and ciprofloxacin (<25%), vancomycin and clindamycin (90%), respectively. Compared with results of other studies, antibiotic resistance pattern of these bacterial strains is variable in different geographical areas; therefore resistant pattern of each group of bacteria must be determined in each area.